Formal synthesis of brivaracetam: a key to construct the pyrrolidone scaffold using Pd-catalyzed oxidative cyclization and ring-closing metathesis reaction - Chavan, Subhash P.; Kawale, Sanket A.; Chavan, Prakash N. (Tetrahedron Letters, 2019)
A short and efficient synthetic approach for brivaracetam has been accomplished via two different routes which utilize Pd-catalyzed oxidative cyclization and ring-closing metathesis (RCM) as the key reaction. These two routes are novel, simple, scalable and rely on (E)-pent-2-en-1-ol and valeraldehyde as a commercially available starting material to yield brivaracetam with good overall yield. (C) 2019 Published by Elsevier Ltd.
Keywords: Antiepileptic drugs; Pd-catalyzed oxidative cyclization; pyrrolinone; Ring-closing metathesis reaction